Cyberbullying Across the Globe 2015
DOI: 10.1007/978-3-319-25552-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Youth Perceptions About Cyberbullying: Qualitative Research into Understanding Cyberbullying and the Role That Parents Play in Its Solution

Abstract: Studies on cyberbullying have been a recurring theme in psychological research over the past 10 years. These studies, as previously occurred with school bullying, have attempted to know the nature of this phenomenon and lower its prevalence, considering the negative consequences for both victims and perpetrators. However, given the epidemiological approach of initial studies, cyberbullying research has predominantly used a quantitative approach where surveys have been the most widely used methodology to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
5
0
2
Order By: Relevance
“…Esta labor es muy importante para prevenir a los menores de los riesgos en la red que tanto impactan en su contexto personal y social (Navarro y Serna, 2016). En los últimos años se han sucedido estudios que tratan de conocer las estrategias que padres y madres ponen en marcha en su labor de supervisión.…”
Section: Introductionunclassified
“…Esta labor es muy importante para prevenir a los menores de los riesgos en la red que tanto impactan en su contexto personal y social (Navarro y Serna, 2016). En los últimos años se han sucedido estudios que tratan de conocer las estrategias que padres y madres ponen en marcha en su labor de supervisión.…”
Section: Introductionunclassified
“…All research team members reviewed the vignette prior to use in the survey. Research has shown that both adolescents and researchers have differing definitions of cyberbullying [ 25 , 34 ]. As such, the term “cyberbullying” was intentionally excluded from the vignette to capture responses that considered broad electronic harassment behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Internet and mobile use as well as the prevalence of electronic harassment in adolescent online communities establish adolescents as key stakeholders in developing electronic harassment interventions. Qualitative approaches to adolescent perspectives on the topic of electronic harassment are growing, and various methodologies exploring adolescent generated solutions have been utilized [ 25 , 26 ]. Some studies have approached this topic using surveys that asked participants to choose from predetermined solutions [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Las consecuencias de este tipo de agresiones son similares a las del bullying tradicional, con especial énfasis de sus dimensiones verbal y psicológica. De hecho, este tipo de actuaciones suelen tener una mayor prolongación en el tiempo al pasar inadvertidas a los familiares, responsables educativos, etc., ocasionando graves consecuencias (Moore, y otros, 2017;Navarro & Serna, 2016). Dado el incremento exponencial que se ha producido en el uso de nuevas tecnologías en los jóvenes adolescentes, ligado al escaso control parental y la inestabilidad propia de la etapa adolescente, el cyberbullying se constituye como un fenómeno de igual o mayor relevancia que el anteriormente mencionado bullying (Elçi, 2016;Garaigordobil, 2013).…”
Section: Introductionunclassified